Icefire - D'Lacey, Chris (New York : Orchard Books, 2005)
While researching the existence of dragons for an essay that could win him a trip to the Arctic, Chris opens himself to the possibility that a great, ancient treasure exists there, guarded by bears, and that he has some role in its protection.
Sequel to: A fire within.
Sequel: Fire star.
G6
Keywords: Supernatural -- Fiction; Dragons -- Fiction; Bears -- Fiction; Boardinghouses -- Fiction; Arctic Regions -- Fiction